IDENTIFICATION OF SCIENTIFIC ARGUMENTATION OF HIGH SCHOOL STUDENTS ON THE ECOSYSTEM TOPICS - R Rosalinda; S Suhendar; S Setiono (Jurnal Pelita Pendidikan, 2021)
This research to determine the profile of the argumentation skills of senior high school (SMA) class XI MIPA 3, students on the ecosystem material that has been learned. By using descriptive method and quantitative approach. The research was conducted at SMAN 2 Sukabumi in the academic year 2020/2021 with a total sample of 13 males and 23 females in class XI MIPA 3. Purposive sampling is a technique for sampling. This research is a description of 22 questions, and research instruments measure the scientific argumentation skills of students. This question refers to the criteria and indicator level for the Toulmin argumentation pattern. The results of the research in class XI MIPA 3 that the students wrote argument ability was still low, this shown by the results of the highest percentage at level 1, namely 26 % and level 2 at 34%. At the same time, the percentage of the argumentation indicator in rebuttal is only 13%. The student's argumentation skills for men with an average score of 48.2 and women's are 67.5. Therefore, the quality of students written arguments is still weak and needs to be improved again by using a learning approach that can train students written argumentation skills.